Towards Canine Rabies Elimination in Cebu, Philippines: Assessment of Health Economic Data. Issue 1 (17th April 2015) - Miranda, L. M.; Miranda, M. E.; Hatch, B.; Deray, R.; Shwiff, S.; Roces, M. C.; Rupprecht, C. E.
Summary: Rabies is endemic in the Philippines. In 2010, with support from the Bill and Melinda Gates Foundation, a canine rabies elimination project was initiated in the Philippine Archipelago of Visayan. We conducted an analysis of dog vaccination and human PEP costs for dog bite patients in a highly urbanized area and a low‐income rural municipality in Cebu Province, Philippines, from 2010 to 2012. Our findings indicated that eliminating rabies in dogs through mass vaccination is more cost‐effective than treating rabies exposures in humans. The average costs (in USD) per human life saved through PEP were 1620.28 in Cebu City and 1498 in Carmen. Costs per dog vaccinated ranged from 1.18 to 5.79 in Cebu City and 2.15 to 3.38 in Carmen. Mass dog vaccination campaigns conducted in each village were more cost‐effective than fixed‐site campaigns. The costs of dog vaccination can be reduced further through bulk vaccine purchase by the national government or large donor agency, for example the BMGF. As communities achieve canine rabies elimination, more judicious use of PEP will result in significant public savings. The study affirms the willingness of local governments to invest and reassure donors of their cooperation and resource contribution to sustain disease elimination efforts.